The menace of caesarean scar pregnancy: a management challenge in modern obstetrics - Choudhary, Anjali; Tanwar, Meenakshi; Nimonkar, Shweta; Singh, Shailly (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: With the increasing caesarean section rates a new challenging evil of caesarean scar pregnancy (CSPs) has emerged. As a variant of ectopic pregnancy caesarean scar pregnancy is the rarest of all. Diagnosis and management of CSP can be challenging especially when there are no early symptoms and even lessor index of suspicion. Objective of this endeavour was to present one institute experience of management of caesarean scar pregnancies. Methods: This are a retrospective analysis of women admitted with CSP. Detailed history, investigation, management protocols and complications were noted. Results: Of the total cases maximum women (60%) had history of previous two caesarean section. 90 % of cases were managed successfully with intra-sac or systemic methotrexate, and surgical evacuation with Foley’s catheter tamponade, only two women needed hysterectomy for uncontrolled bleeding. Conclusions: Caesarean scar pregnancy is a diagnostic and management challenge in modern obstetrics. Early ultrasound diagnosis helps in planning a successful medical treatment and serves to preserve uterus and fertility. Treatment with transabdominal intra-sac methotrexate and Foley’s catheter for tamponade is safe and effective method of treating CSPs.